Disruption of Trip11 in cranial neural crest cells is associated with increased ER and Golgi stress contributing to skull defects in mice. Issue 7 (18th February 2022) - Yamaguchi, Hiroyuki; Meyer, Matthew D.; He, Li; Komatsu, Yoshihiro
Abstract: Background: Absence of Golgi microtubule‐associated protein 210 (GMAP210), encoded by the TRIP11 gene, results in achondrogenesis. Although TRIP11 is thought to be specifically required for chondrogenesis, human fetuses with the mutation of TRIP11 also display bony skull defects where chondrocytes are usually not present. This raises an important question of how TRIP11 functions in bony skull development. Results: We disrupted Trip11 in neural crest‐derived cell populations, which are critical for developing skull in mice. In Trip11 mutant skulls, expression levels of ER stress markers were increased compared to controls. Morphological analysis of electron microscopy data revealed swollen ER in Trip11 mutant skulls. Unexpectedly, we also found that Golgi stress increased in Trip11 mutant skulls, suggesting that both ER and Golgi stress‐induced cell death may lead to osteopenia‐like phenotypes in Trip11 mutant skulls. These data suggest that Trip11 plays pivotal roles in the regulation of ER and Golgi stress, which are critical for osteogenic cell survival. Conclusion: We have recently reported that the molecular complex of ciliary protein and GMAP210 is required for collagen trafficking. In this paper, we further characterized the important role of Trip11 being possibly involved in the regulation of ER and Golgi stress during skull development. Key Findings: Trip11 is expressed in cranial neural crest cells. Trip11 in neural crest cells is critical for developing skull in mice. Trip11 plays pivotal roles in the regulation of ER and Golgi stress, which are critical for osteogenic cell survival.